Marry Me: Using Marital Narratives to Propose Culturally Responsive Practice with Asian Women Who Experience Domestic Violence. Issue 1 (1st January 2016) - Ung, Tien
Abstract : Marriage in Asian communities is a complex cultural phenomenon. There is much to be considered in marital narratives that can deepen our understanding of Asian women's perceptions of health and risk in their intimate unions. The author identifies four contexts garnered from consultation work with an Asian woman's grass-roots organisation associated with the Asian woman's decision to marry. Suggestions are provided around the use of these contexts as points of entry for assessment interviews as part of narrative work to provide an authentic pathway to culturally responsive practice with Asian women affected by domestic violence (DV). A case example is offered to further clarify how marital narratives can be used in assessment, formulation and for case planning with Asian women who are seeking services as a result of DV.